A COMPREHENSIVE REVIEW OF PHYTOCHEMICAL AND PHARMACOLOGICAL OVERVIEW ON CELOSIA CRISTATA FOR FUTURE PROSPECTIVE RESEARCH - SING, MAHAVEER; KUMAR P, SRAVAN; SHRIVASTAVA, BIRENDRA; REDDY B, PAMULA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Celosia cristata (CC) is used in traditional medicine to cure several disorders. It is a member of the genus Celosia and is commonly known as cockscomb, since the flower looks like the head on a rooster. Many sensitive ingredients were isolated from different parts of the plant. The recent studies showed that the plant exerted a wide range of pharmacological activities. The chemical constituents and pharmacological activities of CC were presented in this review.